2023
DOI: 10.3390/diagnostics13061138
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Interventions for Carpal Tunnel Syndrome: A Systematic Review and Meta-Analyses

Abstract: Carpal tunnel syndrome (CTS) is the most common peripheral entrapment, and recently, ultrasound-guided perineural injection (UPIT) and percutaneous flexor retinaculum release (UPCTR) have been utilized to treat CTS. However, no systematic review or meta-analysis has included both intervention types of ultrasound-guided interventions for CTS. Therefore, we performed this review using four databases (i.e., PubMed, EMBASE, Scopus, and Cochrane) to evaluate the quality of evidence, effectiveness, and safety of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 130 publications
(346 reference statements)
1
7
0
Order By: Relevance
“…By contrast, most of the studies on D5W included in this paper used 5 mL, and it is therefore uncertain as to whether an injection volume higher than 5 mL would provide better results. The same conclusion was reached in a systematic review by Lam et al, and CS was found to be superior to lower doses in the high-dose group ( Lam et al, 2023 ). Further research should directly compare different injection volumes of PRP, D5W, and CS to determine their optimal dose.…”
Section: Discussionsupporting
confidence: 75%
“…By contrast, most of the studies on D5W included in this paper used 5 mL, and it is therefore uncertain as to whether an injection volume higher than 5 mL would provide better results. The same conclusion was reached in a systematic review by Lam et al, and CS was found to be superior to lower doses in the high-dose group ( Lam et al, 2023 ). Further research should directly compare different injection volumes of PRP, D5W, and CS to determine their optimal dose.…”
Section: Discussionsupporting
confidence: 75%
“…54,55 However, physicians remain concerned regarding possible steroid-related adverse effects, including hyperglycemia, axonal and myelin degeneration, skin thinning, myopathy, soft tissue atrophy, steroid flares, crystal-induced synovitis, and hypersensitivity reactions. 56,57 In general, the therapeutic effect of perineural steroid injections is relatively short-lived (<3 months) and repeated use is common in clinical practice, amplifying related concerns. [58][59][60] Moreover, alternative medications, such as dextrose or plateletrich plasma, as well as hydrodissection therapy, have been explored; however, their comparative advantage remains controversial owing to different methodologies and conflicting conclusions.…”
Section: Dovepressmentioning
confidence: 99%
“…[58][59][60] Moreover, alternative medications, such as dextrose or plateletrich plasma, as well as hydrodissection therapy, have been explored; however, their comparative advantage remains controversial owing to different methodologies and conflicting conclusions. 56,59,61 Therefore, the development of novel therapeutic agents is of great interest.…”
Section: Dovepressmentioning
confidence: 99%
“…CTS is also considered the most costly and disabling upper-extremity musculoskeletal disorder in Western countries. It causes substantial expenses incurred via medical insurance, lost wages, diminished productivity, and increasing disability in affected individuals [3].…”
Section: Introductionmentioning
confidence: 99%